Reações cutâneas desencadeadas por drogas - Silvares, Maria Regina Cavariani [UNESP]; Lavezzo, Marcelo [UNESP]; Abbade, Joélcio Francisco [UNESP]; Abbade, Luciana Patrícia Fernandes [UNESP]; Gonçalves, Tatiana Maria [UNESP] (FapUNIFESP (SciELO), 2008)
BACKGROUND - Drugs may trigger adverse reactions and skin manifestations are the most frequent ones. OBJECTIVE - To assess drug reactions and report the drugs involved and the most frequent types of skin reactions. METHODS - A retrospective and descriptive study. Data of inpatients at the Dermatology Ward with initial diagnosis of adverse drug reactions were evaluated from January 1999 to June 2004. Patients with confirmed diagnosis were included in the study based on clinical and histopathological criteria, after analysis of medical charts. RESULTS - Initial diagnosis of adverse drug reactions was confirmed in 121 patients. Forty-three patients were included in the study; 51.2% were females and 86% were caucasians. A total of 48.8% were on one drug only. Antibiotics were the most commonly used drug (20%) and accounted for 33% of the drug eruptions. The second group comprised anti-inflammatory drugs (16.7%), followed by anticonvulsants (13%), analgesic/antipyretic (13%) agents. Skin eruption manifested as maculopapular exanthema in 41.9% patients, erythrodermia in 25.6%, and urticaria in 23.3%. CONCLUSION - Maculopapular exanthema was the main type of skin reaction triggered by use of drugs, and these reactions were most frequently caused by antibiotics. ©2008 by Anais Brasileiros de Dermatologia.
Skin reactions to drugs
Keywords: Drug eruptions; Drug hypersensitivity; Exanthema